Malawi’s agrifood system: Transformation and environmental impacts - Diao, Xinshen; Fang, Peixun; Jones, Eleanor; Pauw, Karl; Thurlow, James (International Food Policy Research Institute, 2025)
Agrifood System Diagnostic series presentation prepared June 2025.